2018
DOI: 10.1007/s00125-018-4799-4
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 7 autoantibodies predict progressive decline of beta cell function in individuals with LADA

Abstract: Aims/hypothesis The aim of this work was to investigate whether tetraspanin 7 autoantibodies (TSPAN7A) are valuable in predicting poor beta cell function in individuals with latent autoimmune diabetes in adults (LADA). Methods The cross-sectional study involved participants with LADA (n = 173), type 1 diabetes (n = 158), type 2 diabetes (n = 204) and healthy control participants (n = 170). The longitudinal study involved 53 participants with LADA, with a 3-year follow-up. In both cohorts, TSPAN7A in the sera w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…46,47 All these antibodies are secreted by longlived plasma cells, which are considered to be generated from GCs with the help of Tfh cells, suggesting the aberrant differentiation and function of Tfh cells in T1D patients. So far six major autoantibodies have been identified in T1D: islet cell antibodies (ICA), glutamic acid decarboxylase antibodies (GADA), insulin antibodies (IAA), protein tyrosine phosphatase autoantibodies (IA-2A), zinc transporter 8 antibodies (ZnT8A), and the newly identified tetraspanin 7 antibodies (TSPAN7A).…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dmentioning
confidence: 99%
See 2 more Smart Citations
“…46,47 All these antibodies are secreted by longlived plasma cells, which are considered to be generated from GCs with the help of Tfh cells, suggesting the aberrant differentiation and function of Tfh cells in T1D patients. So far six major autoantibodies have been identified in T1D: islet cell antibodies (ICA), glutamic acid decarboxylase antibodies (GADA), insulin antibodies (IAA), protein tyrosine phosphatase autoantibodies (IA-2A), zinc transporter 8 antibodies (ZnT8A), and the newly identified tetraspanin 7 antibodies (TSPAN7A).…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dmentioning
confidence: 99%
“…Indeed, antigen-experienced memory CD4 + T cells in the blood of T1D patients highly expressed CXCR5, PD-1, ICOS and IL-21, possessing the profile of Tfh. 46,47 Yang and colleagues found that more Tfh cells and elevated levels of IL-21 were observed in ZnT8A or IA-2A-positive T1D patients, which could be reversed after anti-CD20 monoclonal antibody (rituximab) treatment, indicating the essential role of B cells in the maintenance of Tfh cells. Intriguingly, the increase of Tfh cells only occurred in multiple-antibody positive at-risk children.…”
Section: The Aberrant Differentiation and Function Of Tfh Cells In T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously established luciferase immunoprecipitation system assay (LIPS) was used for TSPAN7A testing [4]. Briefly, the TSPAN7-luciferase fusion protein was expressed in 293T cells.…”
Section: Tspan7a Testingmentioning
confidence: 99%
“…T1DM is an organ‐specific autoimmune disease characterized by T cell‐mediated islet ÎČ cell devastation leading to an absolute insulin deficiency (Shi et al, ; Yang et al, ; Zheng et al, ). The preventive effect of FTY720 on autoimmune diabetes was studied in nonobese diabetic mice, a well‐established animal model of spontaneous T1DM.…”
Section: Main Components and Derivatives Of Cordycepsmentioning
confidence: 99%